EFEKTIVITAS KEGIATAN EKSTRAKURIKULER ROHIS TERHADAP PRESTASI BELAJAR MURID DI SMA NEGERI 5 MAKASSAR - Johan, Yongsu; Subaedah; Sampurno, Bambang; Syahid, Akhmad; Akil, M (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the Rohis (Islamic Spiritual Activity) extracurricular program and its contribution to student academic achievement at SMA Negeri 5 Makassar. It employs a qualitative research design with a phenomenological approach. The study was conducted at SMA Negeri 5 Makassar, involving subjects such as the Rohis supervisor, the Rohis chairperson, and Rohis members. Data collection techniques included interviews, observation, and documentation review. The data were analyzed through the stages of collection, reduction, presentation, and conclusion drawing. Data validity was verified using source, technique, and time triangulation. The results indicate that the Rohis extracurricular activities at SMA Negeri 5 Makassar have been effective. This effectiveness is evidenced by structured program planning, activity implementation tailored to students' needs and interests, effective communication and coordination among supervisors, administrators, members, and the school administration, as well as continuous program evaluation. Rohis activities—such as Islamic study sessions, Quranic recitation (tahsin), commemorations of major Islamic holidays, and social service projects—not only enhance religious understanding but also help foster discipline, responsibility, teamwork, self-confidence, and leadership skills among students. Furthermore, Rohis activities contribute positively to student academic achievement, as reflected in improved discipline, motivation, active classroom participation, time management skills, and comprehension of Islamic Religious Education material. Thus, the Rohis extracurricular program serves as a supporting factor in enhancing the student learning process and academic achievement.